2018
DOI: 10.1016/j.juro.2018.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping the Risk of Intermediate Risk Prostate Cancer for Active Surveillance Based on Adverse Pathology at Radical Prostatectomy

Abstract: Adverse pathology at radical prostatectomy was observed at a threefold higher rate in patients classified at favorable intermediate risk compared to low risk, leading to worse overall survival. Men at intermediate risk may be better classified as types 1 and 2 since none showed pathological outcomes similar to those of men at low risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
3
17
1
Order By: Relevance
“…However, recent data from AS programs suggest that IR patients have worse outcomes on AS than LR patients, likely due to the presence of GG2 disease . Furthermore, analyses of a patient cohort at our institution and subsequently a national patient sample demonstrated that compared with patients at LR, those at IR—regardless of risk stratification by individual variables—are several times more likely to harbor adverse pathological findings at RP, which in turn are predictive of worse survival . While previous efforts using cutoffs for separate variables in preoperative risk stratification have failed to identify a subset of biopsy IR patients who may be able to consider AS, our developed multivariable logistic regression model to predict the risk of pathological downgrading has identified a subset of biopsy GG2 IR patients with similar outcomes after RP to biopsy LR patients.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…However, recent data from AS programs suggest that IR patients have worse outcomes on AS than LR patients, likely due to the presence of GG2 disease . Furthermore, analyses of a patient cohort at our institution and subsequently a national patient sample demonstrated that compared with patients at LR, those at IR—regardless of risk stratification by individual variables—are several times more likely to harbor adverse pathological findings at RP, which in turn are predictive of worse survival . While previous efforts using cutoffs for separate variables in preoperative risk stratification have failed to identify a subset of biopsy IR patients who may be able to consider AS, our developed multivariable logistic regression model to predict the risk of pathological downgrading has identified a subset of biopsy GG2 IR patients with similar outcomes after RP to biopsy LR patients.…”
Section: Discussionmentioning
confidence: 89%
“…6,7 However, to our knowledge, there are no data to identify a subset of IR patients who will have a similar outcome on AS to patients at LR. In fact, adverse surgical pathological findings at radical prostatectomy (RP) are several times more likely in IR patients regardless of the definition used 8,9 and are predictive of worse survival. 5,9 Moreover, pathological downgrading or upgrading can occur from biopsy to RP, [10][11][12] further complicating the choice of treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several studies reported that patients with PCa evaluated through biopsy and clinical evaluation with a GG of 2 and favorable intermediate risk harbored a higher grade and stage disease, suggesting that these patients are poor candidates for active surveillance. [25][26][27] Yang et al reported that approximately 1 in 3 of these patients harbored a disease of higher grade or stage. 28 In light of these results, patients with a GG1-graded biopsy would be better candidates than patients with a GG2-graded biopsy for active surveillance instead of curative therapies.…”
Section: Takahiro Inoue Et Almentioning
confidence: 99%